IMPROVING LANGUAGE SKILLS FOR EARLY CHILDHOOD - Daviq Chairilsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Language skills are very important in early childhood development. This literature review aims to provide reinforcement to parents and teachers in order to stimulate language skills in children from an early age. It is necessary applied for children so that the opportunity to make the children’s golden age of 0 to 4 can be realized on both aspects of development, especially in the language improvement. Language improvement in early childhood is not only oriented to the ability to speak alone but also a process that successively starts from listening, speaking, reading, and writing. This is important for children to be improved and optimized since kindergarten, subsequently when taking formal education in elementary, junior, senior high school, and college, children's language skills are in a good category. Meanwhile, these skills are also essential for a career in the future. Parents as the child's closest environment must stimulate and adjust children to speak properly so that language development can be optimal. In addition, teachers also have a very big role in stimulating children through storytelling, question and answer methods, dialogue methods, and many more methods that can be used in stimulating the language development of their students at school.